Interactive architecture : adaptive world - Fox, Michael, 1967 August 22- (2016)
"Architecture has an inherent need to relate to human beings and to nature, the cocreators that have influenced, occupied, traveled through, and appreciated its multitudes of forms. Recent technological developments in biology, computation, cybernetics, engineering, industrial design, material fabrication, and robotics provided the impetus that allowed it to evolve beyond static functionality and become an active participant with the capacity to perceive, react to, and connect with us and with the natural world. Since the process-based guide by Michael Fox and Miles Kemp introduced interactive architecture in 2009, its prototypical potential has been tapped, and is manifest in the eighteen inventive projects featured in this follow-up Architecture Brief. Interactive Architecture: Adaptive World illustrates how the infrastructure within and around which we build our daily lives can process information, make observations, and utilize tools in order to translate natural systems and create seamlessly integrated environments. The structures within run the gamut from data-driven light installations, responsive sculptures, and performative materials to smart highways, dynamic spaces, kinetic facades, and adaptive buildings. In reference to their synergetic nature, they are chaptered according to their prevailing intents to "Exhilarate," "Communicate," "Mediate," "Evolve," and "Catalyze." Contextualized by Fox, expounded upon by the designers/architects, and illuminated by photographs, diagrams, and renderings, Interactive Architecture: Adaptive World bridges the field's antecedent visionaries, present innovations, and future possibilities"--
Keywords: Architecture and technology; Intelligent buildings; Architecture -- Technological innovations